2011
DOI: 10.1111/j.1365-2710.2010.01237.x
|View full text |Cite
|
Sign up to set email alerts
|

Effect of vitamins C and E on antioxidant status of breast-cancer patients undergoing chemotherapy

Abstract: Co-administration of VCE restored antioxidant status, lowered by the presence of breast-cancer and chemotherapy. DNA damage was also reduced by VCE. The results suggest that VCE should be useful in protecting against chemotherapy-related side-effects and a randomized control trial to evaluate the effectiveness of VCE in breast-cancer patients using clinical outcomes would be appropriate.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
47
0
5

Year Published

2011
2011
2024
2024

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 79 publications
(52 citation statements)
references
References 27 publications
(39 reference statements)
0
47
0
5
Order By: Relevance
“…Because ascorbic acid can keep glutathione from becoming oxidized, it can keep the levels of non-oxidized glutathione high in the body, thereby reducing the damage caused by this free radical in its oxidative state. 35 Suhail et al (2012) 35 measured the activity of several different enzymes that scavenge or neutralize free radicals. Comparison between treating twenty breast cancer patients with both chemotherapy and ascorbic acid and another twenty with chemotherapy alone, they found that individuals who also supplemented with ascorbic acid treatment had higher levels of free radical enzymes like glutathione-Stransferase, and glutathione reductase, and had lower levels of DNA damage than those who were administered chemotherapy alone.…”
Section: Discussionmentioning
confidence: 99%
“…Because ascorbic acid can keep glutathione from becoming oxidized, it can keep the levels of non-oxidized glutathione high in the body, thereby reducing the damage caused by this free radical in its oxidative state. 35 Suhail et al (2012) 35 measured the activity of several different enzymes that scavenge or neutralize free radicals. Comparison between treating twenty breast cancer patients with both chemotherapy and ascorbic acid and another twenty with chemotherapy alone, they found that individuals who also supplemented with ascorbic acid treatment had higher levels of free radical enzymes like glutathione-Stransferase, and glutathione reductase, and had lower levels of DNA damage than those who were administered chemotherapy alone.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed there are studies which have previously indicated that AA may also be efficient in treating cancers when used in combination with other active chemotherapeutic drugs. A recent single-arm, multicenter phase 2 study demonstrated that oral consumption of 1 gm of AA in combination with bortezomib and oral melphalan (0.1 mg/kg) is an effective and well tolerated frontline treatment regime for patients with newly diagnosed multiple myeloma [172]. xiv) Reactive oxygen/nitrogen species generated by antineoplastic agents are prime suspects for the toxic sideeffects of acute or chronic chemotherapy.…”
Section: Ascorbic Acid: Evidence Of Transla-tional Efficacy Against Cmentioning
confidence: 99%
“…Durante el tratamiento con citostá ticos se han detectado valores má s elevados de los productos derivados de la peroxidació n lipídica, una reducció n de la capacidad antioxidante total en plasma y de los valores de antioxidantes (vitamina C, E y carotenos), así como una reducció n de los valores tisulares de glutatió n 10,11 .…”
Section: Estré S Oxidativo Inducido Por Tratamientos Oncoló Gicosunclassified